Hound - Freeman, Sam; Romesburg, Sam (Mad Cave Studios, 2024)
During World War I, a young soldier is assigned to one of the most deadly areas along the western front. However, he finds the greatest threat to his life lies not with the enemy, but with a cult formed by his own men.